1985
DOI: 10.1007/bf02541687
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of self degumming properties of phospholipids in soybean oil using HPLC

Abstract: Freshly extracted crude soybean oil was obtained from a commercial soybean oil refinery, divided into aliquots, stored at 24 C and 5 C for varying lengths of time up to two weeks, and analyzed for total phosphorus. The concentrations of phosphatidylethanolamine (PE), phosphatidic acid (PA), phosphatidylinositol (PI) and phosphatidylcholine (PC) were determined by phosphorus analysis following separation by HPLC. Portions of the aliquots were degummed, and total phosphorus and individual phospholipids were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Sample elution was by a 20-min linear gradient to 51:38:11, and a 5-min return to the equilibration solvent. Previous investigators have reported the development of this separation system and its application to the analysis of complex phospholipids from animal, plant and biological lipids (14)(15)(16)(17)(18)(19). The analog signal from the absorption detector was interfaced with a real-time computer (Mod-Comp Inc., Fort Lauderdale, FL) programmed to calculate peak areas and component relative percentage composition.…”
Section: Methodsmentioning
confidence: 99%
“…Sample elution was by a 20-min linear gradient to 51:38:11, and a 5-min return to the equilibration solvent. Previous investigators have reported the development of this separation system and its application to the analysis of complex phospholipids from animal, plant and biological lipids (14)(15)(16)(17)(18)(19). The analog signal from the absorption detector was interfaced with a real-time computer (Mod-Comp Inc., Fort Lauderdale, FL) programmed to calculate peak areas and component relative percentage composition.…”
Section: Methodsmentioning
confidence: 99%
“…Και τα δύο, όμως, εμφανίζουν μειονεκτήματα.Η μη χρήση του χλωροφορμίου προκαλεί προβλήματα στο διαχωρισμό για τον υπερκερασμό των οποίων χρησιμοποιούνται είτε συστήματα βαθμιδωτής έκλουσης είτε σπάνιοι265,266,267 και δύσχρηστοι διαλύτες. Τα δύο, πάντως, βασικά συστήματα που έχουν χρησιμοποιηθεί για το διαχωρισμό με UV των φωσφολιπιδίων είναι αυτά του εξανίου-ισοπροπανόλης -νερού268,269,270,271,272,273,274,275,276 και του ακετονιτριλίου -μεθανόλης -νερού 277,278,279,280,281,282. Το πρώτο χρησιμοποιείται περισσότερο σε σύστημα βαθμιδωτής έκλουσης και το δεύτερο σε ισοκρατικό με διαλύματα οξέων283 (φωσφορικού284,285,286 ή θειικού 287 ) ή αλάτων (κυρίως φωσφορικών) αντί νερού.…”
unclassified